Peningkatan Pemahaman dan Adopsi Teknologi Keuangan pada UMKM melalui Program Pengabdian di Kota Samarinda - Muhammad Astri Yulidar Abbas; Siti Maulina; Putri Indardaini (Yayasan Literasi Sains Indonesia, 2025)
This Community Service (Pengabdian kepada Masyarakat) aims to enhance the understanding and adoption of financial technology (fintech) among Micro, Small, and Medium Enterprises (MSMEs) in Samarinda City. Advances in fintech, such as digital wallets, peer-to-peer lending, and digital payments, offer significant potential to improve capital access, operational efficiency, and expand MSMEs' market reach. However, varying digital and financial literacy often becomes a primary obstacle to utilizing these innovations. Using a qualitative approach, this study involves in-depth interviews with several MSME actors across various sectors. The data collected includes their perceptions of fintech's benefits and risks, usage experiences, and encountered challenges, such as data security issues and interface complexity. The results of this Community Service are expected to provide a comprehensive overview of the fintech understanding profile of Samarinda's MSMEs. Strategic recommendations will be formulated for local governments, financial institutions, and fintech service providers to design more relevant and inclusive educational programs, aiming to foster sustainable digital financial inclusion within the MSME sector.